The First Ground‐Level Enhancement of Solar Cycle 25 as Seen by the High‐Energy Particle Detector (HEPD‐01) on Board the CSES‐01 Satellite - Matteo Martucci; Monica Laurenza; Simone Benella; Francesco Berrilli; Dario DelMoro; Luca Giovannelli; Alexandra Parmentier; Mirko Piersanti; Gabor Albrecht; Simona Bartocci; Roberto Battiston; William J. Burger; et al. (Space Weather)
Abstract In this work we present the High‐Energy Particle Detector (HEPD‐01) observations of proton fluxes from space during the 28 October 2021 solar energetic particle event, which produced a ground‐level enhancement on Earth. The event was associated with the major, long‐duration X1‐class flare and the concomitant coronal mass ejection (CME) that erupted from the Active Region 12887. This is the first direct measurement from space of solar particles emitted during the current solar cycle, recorded by a single instrument in the energy range from ∼50 MeV/n up to ∼250 MeV/n. We have performed a Weibull‐modeled spectral analysis of the energy spectrum in the wide energy range 300 keV–250 MeV, obtained from combination of HEPD‐01 proton measurements with the ones from ACE/ULEIS, SOHO/EPHIN, and SOHO/ERNE. The good agreement between data and model, also corroborated by a comparison with other spectral shapes commonly used in these studies, suggests that particles could have possibly been accelerated out from the ambient corona through the contribution of stochastic acceleration at the CME‐driven shock, even if the presence of seed populations influencing spectral shape could not be excluded. Finally, a Solar Proton Release time of 16:01 UTC ± 13 min and a magnetic path‐length of L = 1.32 ± 0.24 AU have been obtained, in agreement with previous results for this event. We remark that new and precise data on protons in the tens/hundreds MeV energy range—like the one provided by HEPD‐01—could shed more light on particle acceleration as well as provide a reliable parametrization of solar energetic particle spectra for Space Weather purposes.